Assimilação de conceitos relacionados a triângulos e quadriláteros através da robótica educativa - Rüedel, Alessandra Cristina (2019)
The present research brings as main motivation the too many cases of disinterest on the part of the students in the mathematical learning, searching in this way an engaging and technological environment, with potential to arouse in them the curiosity and effective desire for the mathematical knowledge, instigating the construction of a more learning. lasting and significant. In this sense, the following question was formulated: “How can Educational Robotics be used to understand mathematical knowledge, especially some elements of flat Euclidean geometry, such as triangles and quadrilaterals?” In order to answer this question, subsidies were sought in the areas STEM (Science, Technology, Engineering and Mathematics), supported by Seymour Papert's theory (constructionism), where learning occurs through student interaction with objects, in this case with programmable electronic devices. Before that, the objective of this research, through a didactic sequence, is to evaluate the relevance of the use of Educational Robotics as a resource in the teaching of mathematical content, more specifically in Euclidean geometry, especially triangles and quadrilaterals. This research uses predominantly the qualitative approach, with intervention of the action research type, being considered as instruments for data collection the logbook, questionnaires and materials produced by the students. In the analysis of the results it was possible to notice that the use of technologies as a didactic resource helps in the construction / assimilation of knowledge, considering that the students were really attracted and interested in the activities, clearly noting the enthusiasm with the practical examples and the robot. As well as the excitement of feeling challenged with each activity. We can also highlight that the work in pairs provided the opportunity for analysis and dialogue on the resolutions, thus working to rescue and jointly fix the concepts already studied. This dissertation is accompanied by an Educational Product, in the form of a didactic sequence aimed at teachers, which describes a possibility of using Educational Robotics as a resource in math classes, specifically in the assimilation of the contents of triangles and quads. This product is available at website: <http://educapes.capes.gov.br/handle/capes/559603>.